Arterial Hypertension, Metabolic Syndrome and Subclinical Cardiovascular Organ Damage in Patients with Asymptomatic Primary Hyperparathyroidism before and after Parathyroidectomy: Preliminary Results - Petramala Luigi; Formicuccia Maria Chiara; Zinnamosca Laura; Marinelli Cristiano; Cilenti Giuseppina; Colangelo Luciano; Panzironi Giuseppe; Cerci Sabrina; Sciomer Susanna; Ciardi Antonio; Cavallaro Giuseppe; De Toma Giorgio; et al. (International Journal of Endocrinology)
Background. Primary hyperparathyroidism (PHPT) is associated with high cardiovascular morbidity, and the role of calcium and parathyroid hormone is still controversial. Objective. To evaluate the prevalence and outcomes of metabolic syndrome, hypertension, and some cardiovascular alterations in asymptomatic PHPT, and specific changes after successful parathyroidectomy. Material and Methods. We examined 30 newly diagnosed PHPT patients (8 males, 22 females; mean age 56±6 yrs), 30 patients with essential hypertension (EH) (9 males, 21 females; mean age 55±4), and 30 normal subjects (NS) (9 males, 21 females: mean age 55±6). All groups underwent evaluation with ambulatory monitoring blood pressure, echocardiography, and color-Doppler artery ultrasonography and were successively revaluated after one year from parathyroidectomy. Results. PHPT patients presented a higher prevalence of metabolic syndrome (38%) with respect to EH (28%). Prevalence of hypertension in PHPT was 81%, and 57% presented altered circadian rhythm of blood pressure, with respect to EH (35%) and NS (15%). PHPT showed an important myocardial and vascular remodelling. During follow-up in PHPT patients, we found significant reduction of prevalence of metabolic syndrome, blood pressure, and “non-dipping phenomenon.” Conclusions. Cardiovascular and metabolic alterations should be considered as added parameters in evaluation of patients with asymptomatic PHPT.